Report on the First Inter-American Trade Union Economic Conference : (São Paulo, Brazil, august 17-19, 1961) (Inter-Amerian Trade Union Economic Conference (1°. São Paulo. 1961))
Precede al tít.: ORIT-ICFTU Special Publications